Implikasi Komunikasi dalam Pendidikan terhadap Pembentukan Karakter Santri di YPP Sunan Kalijaga Surabaya - Mas Nur Zubaidah; Lailatul Masyfirah (Al-Balagh : Jurnal Komunikasi Islam, 2023)
This research aims to describe and examine the phenomenon of "educational communication" at YPP Sunan Kalijaga Surabaya, particularly in the context of building "student character." At the end of the paper, the results are presented, which show that "educational communication" has been implemented at the Yayasan Pondok Pesantren Sunan Kalijaga Surabaya, especially between the teacher, ustaz and ustazah, and the santri (students). This educational communication is critical because, to achieve the foundation's goals, good communication between the teacher and the students must be developed, in addition to the significant role that teachers play in the process of education and learning of students. Language is an essential aspect of communication since it can shape the character of the students. For example, conversing in Javanese kromo or kromo inggil provides the students with a refined character and respect for others. This effective communication has an impact on the students’ character, particularly personality and disciplinary traits. The challenges include: (1) communication misunderstandings, (2) students’ lack of insight, and (3) teenage students who are in the age of self-discovery and are easily influenced by their surroundings.